High-speed rail effects on station area-level business commercial agglomeration: Evidence from 110 stations in China - Liang, Pengpeng; Cui, Xu; Lin, Mao; Yang, Tian; Wu, Bo (Frontiers in Environmental Science, 2022)
As a critical transportation infrastructure, high-speed rail (HSR) greatly enhances accessibility and shortens the spatial-temporal distance among cities. It is well documented that HSR significantly im-pacts regions and cities’ economic development and spatial structure. The proportion and frequency of business passenger trips are increasing yearly, and the demand for "station as the final destination" is becoming more and more prominent. Given the pivotal role of the design and construction of HSR station areas in achieving "station as the final destination," the study of their development characteris-tics and patterns has important implications for urban planning. Previous studies have focused exten-sively on the macro impact of the HSR operation on regional economies, urban industries, and tour-ism development, whereas only a few were conducted at the station level. Furthermore, the business-commercial agglomeration effects of the HSR operation on the development and construction of sta-tion areas have neither been studied nor accurately measured. To fill this gap, we first constructed a panel data set consisting of the point of interest (POI) data, China City Statistical Yearbook data, and the HSR station operation data from 2012 to 2017. Next, we developed difference-in-differences (DID) models to decipher the impact of the HSR operation on the station-level business and commercial agglomeration. The results show that the HSR operation has increased the business-commercial agglomeration index (BCAI), the commercial agglomeration index (BAI), and the busi-ness agglomeration index (CAI) by 28.3%, 29%, and 21.3%, respectively. In other words, the HSR operation has significant business-commercial agglomeration effects in the station area, and the ag-glomeration effect size of business is more extensive than that of commerce. Interestingly, the BCAI grew slowly in the first three years after the HSR operation but started to rise much faster from the fourth year, which HSR’s catalytic effects can explain. The results also reveal that the business-commercial agglomeration effects have a clear spatial threshold as the BCAI tends to decrease from 1500m to 3000m away from HSR stations. The plausibility of the results has been confirmed by the parallel trend, placebo, and robustness tests.